Gambaran Perilaku Sehat Pada Remaja Awal Di SMP Muhammadiyah I Kartasura - Sama, Soffat, Siti Arifah, S.Kp, M.Kes, Enita Dewi, S.Kep.,Ns.,MN (2015)
Health behaviors is an activity undertaken by individuals or groups that are intended to avoid health problems. One part of the health behaviors are preventive behaviors, it's intended to minimize the risk or likelihood of disease, and accidents. The purpose of this study is to describe health behaviors of early adolescents at Muhammadiyah I Kartasura Junior High School. The type of this research is non-experimental research with survey descriptive method and quantitative approaches. The samples were 83 students in year VII, VIII, IX of Muhammadiyah I Kartasura Junior High School. The data processing using descriptive techniques. This research found that: (1) the motorcycle rider behavior appeared that respondents are motorcyclist (61%) and as pillion passenger (76%), respondent wearing a helmet (52%) , do not consume alcohol (96%) and do not use a mobile phone (87%) while riding a motorcycle (2) the smoking behavior of this study are appeared that respondent who smoke is 33% motivated by want to try, due to the supporting factors including family members and peers who smoke (3) The violence behavior of this research are appeared that respondent not carrying weapons out of the house is 94%, do not carrying weapons to school is 88%, and never got into a fight during the last 6 months is 79% ever got fought is 21%. The health behaviors of Muhammadiyah I Kartasura Junior High School is good due to the result appeared.